The effect of learning independence on mathematics learning achievement seventh grade of junior high school students - Afrida Yanti; Muhamad Sofian Hadi (Universitas Sarjanawiyata Tamansiswa, 2023)
The low independence of student learning, especially in mathematics lessons, is a driver for research. Based on observations, most students do not realize the importance of learning independence. Many students don't want to learn math, and most don't like it because they think math is too difficult. Survey methods with simple regression analysis are used in research. The study aims to determine the effect of independence on mathematics learning achievement of seventh grade students at State Junior High School 7 Bekasi City in the even semester of the 2022/2023 academic year. Sampling using a simple random sampling technique with 38 students from seventh grade at Junior High School 7 Bekasi City. Data analysis using the help of the Statistical Program for Social Science (SPSS) 22 program with stages of descriptive statistical analysis, testing prerequisites for data analysis (normality test, linearity test, and hypothesis test). The results of the study can be concluded that there is an influence of independence on mathematics learning achievement in seventh grade of junior high school students. The effect of independence on students' mathematics learning achievement was 10.4%, and 89.6% was influenced by other factors.